Relationship between cardiac deformation parameters measured by cardiovascular magnetic resonance and aerobic fitness in endurance athletes. Issue 1 (December 2016) - Swoboda, Peter; Erhayiem, Bara; McDiarmid, Adam; Lancaster, Rosalind; Lyall, Gemma; Dobson, Laura; Ripley, David; Musa, Tarique; Garg, Pankaj; Ferguson, Carrie; Greenwood, John; Plein, Sven
Abstract Background Athletic training leads to remodelling of both left and right ventricles with increased myocardial mass and cavity dilatation. Whether changes in cardiac strain parameters occur in response to training is less well established. In this study we investigated the relationship in trained athletes between cardiovascular magnetic resonance (CMR) derived strain parameters of cardiac function and fitness. Methods Thirty five endurance athletes and 35 age and sex matched controls underwent CMR at 3.0 T including cine imaging in multiple planes and tissue tagging by spatial modulation of magnetization (SPAMM). CMR data were analysed quantitatively reporting circumferential strain and torsion from tagged images and left and right ventricular longitudinal strain from feature tracking of cine images. Athletes performed a maximal ramp-incremental exercise test to determine the lactate threshold (LT) and maximal oxygen uptake (V̇O2max ). Results LV circumferential strain at all levels, LV twist and torsion, LV late diastolic longitudinal strain rate, RV peak longitudinal strain and RV early and late diastolic longitudinal strain rate were all lower in athletes than controls. On multivariable linear regression only LV torsion (beta = −0.37, P  = 0.03) had a significant association with LT. Only RV longitudinal late diastolic strain rate (beta = −0.35, P  = 0.03) had a significant association with V̇O2max . Conclusions This cohort of endurance athletes had lower LV circumferential strain, LV torsion and biventricular diastolic strain rates than controls. Increased LT, which is a major determinant of performance in endurance athletes, was associated with decreased LV torsion. Further work is needed to understand the mechanisms by which this occurs.